The Safety of 250 µm Residual Stromal Bed in Preventing Keratectasia after Laser in situ Keratomileusis (LASIK) - Kim, Tae Ho (The Korean Academy of Medical Sciences, 2007)
To determine if the residual corneal stromal bed of 250 µm is enough to prevent iatrogenic keratectasia in laser in situ keratomileusis (LASIK), we studied 958 patients who underwent LASIK from April 2000 to October 2003 retrospectively. The estimated probabilities of the residual stromal bed, that was less than 250 µm, were calculated using the publi- shed flap thickness data of Moria C&B microkeratome. Then we calculated the ratio of the real incidence of keratectasia to the expected the percentage of the patients with less than 250 µm residual stromal bed in our study. Using the LASIK flap thickness data of Miranda, Kezirian and Nagy, the expected probabilities that the residual stroma would be less than 250 µm were 8.8%, 4.3% and 1.5% of the 1,916 eyes respectively, while keratectasia developed in both eyes (0.1%) of 1 patient in our study. The estimated ratio of the keratectatic eyes to eyes with less than 250 µm stromal bed were 1.2-6.9%. Compared to the number of eyes with residual stromal thickness less than 250 m, the incidence of keratectasia was relatively low. The residual stromal bed thickness of more than 250 µm may possibly be safe, but further observations for long period are necessary.